Puréed Foods: A Guide to Quick Meals - Wendy J. Dahl (EDIS)
Puréed foods are an important source of nutrients for those who have problems chewing or swallowing. A puréed food is any item that has been processed into a smooth and uniform texture and therefore does not require chewing. Purées can be made from most foods and this guide provides some tips for fast and easy to prepare puréed foods. This 4-page fact sheet covers the preparation of puréed foods from canned vegetables and fruits; beans, peas, and lentils; and mixed dishes. It also provides a useful example meal plan. Written by Wendy J. Dahl, and published by the Food Science and Human Nutrition Department, March 2016.